Slow oocyte freezing and thawing in couples with no sperm or an insufficient number of sperm on the day of in vitro fertilization - Tomazevic Tomaz; Bacer-Kermavner Liljana; Virant-Klun Irma; Vrtacnik-Bokal Eda (BMC, 2011)
Abstract Background The clinical results of in vitro fertilization of slowly frozen-thawed oocytes are known to be significantly worse than those obtained by fresh oocytes. Little is known about the factors affecting the clinical outcome of frozen-thawed oocytes. The aim of this retrospective study was to explore the role of oocyte cryopreservation in the group of patients with no available sperm on the day of in vitro fertilization. Additionally, the effects of the female serum FSH level and sperm quality on the clinical outcome of frozen-thawed oocytes were evaluated. Methods Oocytes were slowly frozen and thawed in 22 infertile couples with no sperm or insufficient number of sperm on the day of in vitro fertilization (IVF). In 9 couples with severe azoospermia or oligoasthenoteratozoospermia frozen-thawed oocytes were fertilized by autologous sperm of bad quality when available (Group 1). In 13 couples with non-ejaculation due to psychological stress on the day of classical IVF or severe azoospermia frozen-thawed oocytes were fertilized by autologous or donated sperm of normal quality (Group 2). Oocytes were thawed in 23 cycles and microinjected by the autologous or donated sperm, when available. The clinical outcome of intracytoplasmic sperm injection - ICSI (fertilization, blastocyst, and pregnancy rates) was compared to the outcome of fresh oocytes of the same group of patients; additionally, the female serum FSH level and the sperm quality were compared. Results In all couples, 70.5% of oocytes survived the freeze-thaw procedure. After ICSI, 61.5% of thawed oocytes were fertilized. Twenty one% of embryos developed to the blastocyst stage. The pregnancy rates per embryo transfer and freeze-thaw cycle were 33.3% and 17.4%, respectively. All pregnancies ended in the birth of a baby without congenital anomalies. In patients with severe azoospermia or oligoasthenoteratozoospermia there was no statistically significant difference in pregnancy rates per cycle obtained by thawed oocytes vs. fresh oocytes in previous ICSI cycles (14.2% vs. 13.6%) but there was a higher proportion of abnormal, non-cleaved or triploid zygotes when frozen-thawed oocytes were microinjected (33.3% vs. 11.8%; P < 0.01). The female serum FSH levels did not affect the survival and fertilization of frozen-thawed oocytes, but in patients with increased serum FSH level no pregnancies were achieved. After the complete freeze-thaw cycle, there was a significantly higher fertilization rate and tendency to higher pregnancy rates per thawing cycle after the microinjection of autologous or donated sperm of normal quality than autologous sperm of poor quality. Conclusion The slow oocyte freezing and thawing is a valuable method when no or insufficient number of sperm are available on the day of in vitro fertilization. The quality of sperm is an important factor affecting the clinical outcome achieved by frozen-thawed oocytes.